Rheological study of the curing kinetics of epoxy-phenol novolac resin - Auad, María L. (2006)
The curing reaction of an epoxy-phenolic resin under different conditions was monitored using rheological measurements. The evolution of viscoelastic properties, such as storage modulus, G′, and loss modulus, G″, was recorded. Several experiments were performed to confidently compare the rheological data obtained under varied curing conditions of temperature, catalyst concentration, and reactive ratios. The values of G′ measured at the end of the reactions (at maximum conversion) were independent of the frequency and temperature of the tests in the range of high temperatures investigated. The overall curing process was described by a second-order phenomenological rheokinetic equation based on the model of Kamal. The effects of the epoxy-to-phenolic ratio as well as the curing temperature and the catalyst concentration were also investigated.